2017
DOI: 10.1007/s10388-017-0601-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the herbal medicine Daikenchuto (TJ-100) after esophageal cancer resection, open-label, randomized controlled trial

Abstract: Background Daikenchuto (TJ-100), a traditional Japanese herbal medicine, is widely used in Japan. Its effects on gastrointestinal motility and microcirculation and its anti-inflammatory effect are known. The purpose of this prospective randomized controlled trial was to investigate the effect of TJ-100 after esophagectomy in esophageal cancer patients.MethodsForty patients for whom subtotal esophageal resection for esophageal cancer was planned at our institute from March 2011 to August 2013 were enrolled and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Of these, 753 articles were excluded, resulting in 60 that met the selection criteria and 5603 enrolled participants (of whom 5261 were analyzed). 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 753 articles were excluded, resulting in 60 that met the selection criteria and 5603 enrolled participants (of whom 5261 were analyzed). 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ...…”
Section: Resultsmentioning
confidence: 99%
“…The durations of follow-up ranged from 1 to 60 months (median, 12 months). A total of 21 studies were from Western Europe, 25 , 27 , 41 , 54 , 61 , 62 , 65 , 72 , 81 , 82 , 84 11 from North America, 25 , 27 , 41 , 54 , 61 , 62 , 65 , 72 , 81 , 82 , 84 9 from East Asia, 29 , 38 , 39 , 44 , 51 , 52 , 60 , 66 , 68 5 from South America, 28 , 69 , 78 , 79 , 83 5 from Western Asia, 28 , 69 , 78 , 79 , 83 and 3 each from Africa, 35 , 50 , 76 the Pacific, 26 , 42 , 75 and Eastern Europe. 45 , 74 , 80 …”
Section: Resultsmentioning
confidence: 99%
“…As for the mechanism of the increase and maintenance and gain of body weight in the TJ-100 group, there are some possible reports to support our results. The positive effects of TJ-100 after esophageal cancer resection were reported in an open-label, randomized controlled trial after esophageal surgery [7]. It stated that TJ-100 plus nutritional agents enhanced recovery after esophageal surgery.…”
Section: Control Group N=8mentioning
confidence: 97%
“…Table 3C shows an RCT of Kampo medicine for the perioperative period. Nishino et al reported the effects of DKT after esophageal cancer resection in an RCT that included elderly subjects (53). The rate of weight loss at postoperative day 21 was significantly suppressed in the DKT group.…”
Section: Constipationmentioning
confidence: 99%